SOCIAL REPRESENTATION AND ETHICAL COMMUNICATION IN CONTEMPORARY ISLAMIC PREACHING (A Content Analysis of Gus Miftah’s Viral Video on the Sweet Iced Tea Seller Incident) - Fauzi, Winda Kustiawan; Afdal Hafiz Takar; Salman Kanz; Fauzi, Rizky Adi Candra Nasution (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study is motivated by significant changes in da’wah (Islamic preaching) practices in the digital era, where social media has become a new space for preachers to deliver religious messages, while also presenting complex ethical and social meaning challenges. The viral video of Gus Miftah involving a sweet iced tea vendor serves as a concrete example of how a da’wah message can generate controversy due to its social representation and communicative style. Using Stuart Hall’s theory of representation, this research aims to analyze how meaning is constructed, conveyed, and interpreted within the context of contemporary da’wah, and how communication ethics and local cultural values are reflected in the process. This study employs a qualitative approach with a descriptive qualitative research type and a qualitative content analysis design. Data were collected through documentation and archival analysis of the video content and digital sources. The findings reveal that the social meaning in Gus Miftah’s da’wah shifts through an encoding–decoding mechanism, where the term “goblog” undergoes reinterpretation when transferred to the digital realm. His egalitarian and humorous discursive practice becomes problematic when faced with a culturally diverse virtual audience. The da’wah reflects tensions between local wisdom and the universal values of Islam. This study recommends the development of digital da’wah strategies that are more sensitive to audience diversity and emphasizes the need for reinterpretation of preaching methods that align with Islamic communication ethics in modern public spheres.